1996
DOI: 10.1093/jac/37.1.93
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro effects of cefodizime of leucocyte functions and colony formation from granulocyte-monocyte progenitors

Abstract: Infections in immunocompromised patients are often difficult to treat, even with currently available antimicrobial agents. An understanding of the effects of antibiotic therapy on the host's immune response is therefore important when deciding on the clinical management of such patients. Antimicrobial agents which lack immunodepressive effects and/or potentiate the immune response are the goal of current research into the treatment of infections in immunocompromised patients. The effects of cefodizime (1-250 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has been shown that in vitro, cefodizime stimulates the proliferative response of lymphocytes, increases the phagocytotic and bactericidal activity of PMNs, and downmodulates the production of proinflammatory cytokines by stimulated monocytes. In contrast to all ␤-lactams, cefodizime was also reported to significantly increase colony formation by granulocyte-monocyte progenitors (353). Alteration of bacterial virulence in susceptible and resistant bacteria has also been demonstrated with cefodizime.…”
Section: Immunostimulation or Restoration?mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in vitro, cefodizime stimulates the proliferative response of lymphocytes, increases the phagocytotic and bactericidal activity of PMNs, and downmodulates the production of proinflammatory cytokines by stimulated monocytes. In contrast to all ␤-lactams, cefodizime was also reported to significantly increase colony formation by granulocyte-monocyte progenitors (353). Alteration of bacterial virulence in susceptible and resistant bacteria has also been demonstrated with cefodizime.…”
Section: Immunostimulation or Restoration?mentioning
confidence: 99%
“…The loss of interest in IRM antibiotics is clearly illustrated by the drastic fall in publications relevant to this drug. More than half the publications on cefodizime were published in 1984 to 1990, whereas only five papers were referenced in 1996 to 1999 (28,29,38,71,353).…”
Section: Immunostimulation or Restoration?mentioning
confidence: 99%
“…It has been shown that in vitro, cefodizime stimulates the proliferative response of lymphocytes, increases the phagocytotic and bactericidal activity of PMNs, and downmodulates the production of proinflammatory cytokines by stimulated monocytes. In contrast to all ␤-lactams, cefodizime was also reported to significantly increase colony formation by granulocyte-monocyte progenitors (353). Alteration of bacterial virulence in susceptible and resistant bacteria has also been demonstrated with cefodizime.…”
Section: Immunostimulation or Restoration?mentioning
confidence: 99%
“…The loss of interest in IRM antibiotics is clearly illustrated by the drastic fall in publications relevant to this drug. More than half the publications on cefodizime were published in 1984 to 1990, whereas only five papers were referenced in 1996 to 1999 (28,29,38,71,353).…”
Section: Immunostimulation or Restoration?mentioning
confidence: 99%